Forensic Accounting Maturity Model in Iran - Zohre Abbas Tafreshi; Gholamreza Soleimany Amiri (پژوهش‌های تجربی حسابداری)
The main purpose of this research is to present the maturity model of forensic accounting in Iran in order to identify and evaluate the dimensions and components affecting forensic accounting in Iran by providing a desirable and evolutionary model using the five-level maturity model of integrated maturity capability (CMMI) and the path of professional excellence and reaching higher levels will be specified with the leveling of components and finally it can be a guide for the necessary actions of professional members and trustees to reach the best status of the profession.The method of conducting the research is based on the objective of the applied type, and in terms of its nature, it is a qualitative research, and data collection was done using interviews. So that initially by studying documents and articles, the primary dimensions and components affecting the maturity of forensic accounting in Iran were identified. In the next stage, semi-structured interviews were conducted between 2023 and 2024 with twenty-one academic and professional accounting experts and official accounting justice experts who were selected using snowball sampling. By using the interviews, some of the identified dimensions and components were reviewed. After conducting interviews with experts and reaching theoretical saturation by the researcher, the data obtained from the interviews were analyzed and coded using theme analysis, and the dimensions of the forensic accounting maturity model in Iran were identified and presented to the owner. The comments were refined and approved. Based on this, the dimensions of Iran's forensic accounting maturity model include services and roles, professions and institutions, human resources, information technology, reporting, continuous improvement, service quality assurance, each of which was presented in five levels in the current research. The results of this research provide a comprehensive framework to evaluate the forensic accounting profession in Iran and will play an effective role in improving the status of the profession and can be used as a benchmark for planning the members of the profession.